Biased Through-Deck Blasthole Samples Created By Clay Gouge At The Lone Tree Mine, Humboldt County, Nevada - T. Panhorst (Society for Mining, Metallurgy & Exploration, 1999)
Evaluation of through-deck blasthole sample reliability at the Lone Tree gold mine revealed a non-systematic bias in the sampling system. Ore is primarily hosted within the Powerline fault zone. Clay gouge, present in the fault zone and typically enriched in gold content, forms agglomerates during blasthole drilling leading to a segregation error during sampling. Replicated samples split from blasthole cuttings piles show through-deck samples to be either significantly enriched or depleted by 1.5 standard deviations or more from the mean gold content of their respective cuttings pile quality of through-deck samples correlates strongly with quantity of clay present.